Planning and Organization of High School Activities with Google Classroom Asysyakirin Tangerang Islamic High School Training Participants - Reni, Reni Utami; Ari Hidayatullah (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2024)
The PKM implemented aims to train high school students to use Google Classroom media for the teaching and learning process in the current hybrid era, after the Covid-19 pandemic. With this training, students and teachers can optimize their use of Google Classroom more optimally and efficiently because they have previously used it. The first stage was to explore problems related to the potential of e-learning during the Covid-19 pandemic. 3 years ago, this activity resulted in an increase in students' knowledge about e-learning and skills in using Google Class Room in the current era. Classes are an online learning medium that is interactive and fun in the teaching process and collecting assignments